Creating exhibitions : - McKenna-Cress, Polly. (Wiley, 2013)
Structured around the key phases of the exhibition design process, this guide offers complete coverage of the tools and processes required to develop successful exhibitions. Intended to appeal to the broad range of stakeholders in any exhibition design process, the book offers this critical information in the context of a collaborative process intended to drive innovation for exhibition design. It is indispensable reading for students and professionals in exhibit design, graphic design, environmental design, industrial design, interior design, and architecture